Grid connected photovoltaic system impression on power quality of low voltage distribution system. Issue 1 (31st December 2022) - Salem, W.A.A.; Gabr Ibrahim, Walaa; Abdelsadek, Aya M.; Nafeh, A. A.
Abstract: To ensure the global energy demands and decarbonize the production of electricity, the expanded utilization of solar photovoltaics (PV) as a renewable energy resource has been increasing in recent decades, principally with the feasibility to be integrated with the conventional power grid. However, supplying clean power from PV grid-connected systems is often hampered by power quality (PQ) disturbances caused by the intermittent nature of solar radiation and other factors related to the grid, converters, and connected loads. To prevent deterioration of the power quality of the system, these disturbances must be mitigated. This paper technically studies some of these PQ issues, that is, the current total harmonic distortion (THD) which causes harmful effects on the whole connected power system and the linked loads. The case study works on a 5.5 kW grid-connected rooftop PV power system established at Benha Faculty of Engineering, Egypt, with the assistance of an installed weather station that boosts the validation of the research results. All aspects regarding the aforementioned small plant are presented including description and simulation of the whole system, review of current THD problems occurring at the point of common coupling (PCC), and a review of other disturbances observed by connected meters. A detailed examination of four techniques for harmonic mitigation, namely the on-off technique, LCL filter, active power filter, and hybrid active power filter is presented with a final comparison to assess the merits and demerits of each one. This research achieved a current harmonic limitation of 1.5%.